La inflación importada vía precios del petróleo, caso de estudio Ecuador, periodo 2000-2021. - Betancourt Sánchez, Genesis Lizbeth (2023)
Oil is a necessary good the variation in its price results in an inflationary process that affects all economic sectors and emerging economies. Considering this background, the main objective of this research is to determine the causal relationship between oil prices and inflation in Ecuador from January-2000 to December-2021. The VAR autoregressive vector model was used, whose variables are oil prices about those of the West Texas Intermediate (WTI) and consumer price index (CPI). The main results achieved in the study establish that there is a slight influence of crude oil prices on inflation. It is mainly due to state subsidies imposed on fuels and the exchange rate used by Ecuador. Additionally, it was found that there is no bidirectional causality between oil prices and imported inflation.